Digital Approach in Optimizing Conservation Agriculture Practices - Judijanto, Loso (West Science Agro, 2025)
The integration of digital technologies in conservation agriculture (CA) has emerged as a transformative approach to enhancing agricultural sustainability and productivity. This qualitative study explores the experiences of five farmers implementing CA practices supported by digital tools. Semi-structured interviews reveal the benefits of digital adoption, including improved resource efficiency, enhanced productivity, knowledge dissemination, and environmental sustainability. However, challenges such as limited digital literacy, high costs, and poor rural internet connectivity hinder broader adoption. The study discusses these findings in the context of existing literature, emphasizing the need for user-friendly technologies, capacity building, and infrastructure development. The research concludes with policy and practical recommendations to bridge the gap between technology and farmers, ensuring equitable access and maximizing the potential of digital tools to optimize CA practices.